The role of ideations in de-problematizing migration crises (and other wicked problems) - Klasche, Benjamin (Frontiers in Political Science, 2023)
This article examines the role of ideations in the de-problematization process of the governance of “migration crises”. Ideations, for example, in the form of frames often simplify social reality and do not allow us to understand the nature of a problem policy-makers are dealing with. To show this, I use the example of the “European Migrant Crisis,” to illustrate that it is, in fact, a wicked problem. The “wicked problem” concept describes a complex and contingent problem and, in essence, a set of “un-owned” processes. It further dissolves local and global distinctions and forces to connect micro and macro processes at all times. In this article, I show that this “migration crisis” (and also many others) consists of much more than just a humanitarian or security crisis but is also constituted by geopolitical crises and crises of political institutions. A relational approach seems most pertinent to be able to grasp all these aspects and helps us to stop de-problematizing it and instead problematize it adequately. It also advocates for the circumvention of ideations as they are a main source for the de-problematization of wicked problems.